Association between glenohumeral subluxation and hemiplegic shoulder pain in patients with stroke. (1st April 2013) - Kumar, Praveen; Saunders, Amanda; Ellis, Emily; Whitlam, Sarah
<x xml:space="preserve">Abstract</x> Background: Glenohumeral subluxation (GHS) and hemiplegic shoulder pain (HSP) are the most common musculoskeletal complications reported in patients with stroke. These secondary problems present considerable challenges to the rehabilitation of the upper limb. Objective: The aim of this review was to evaluate the evidence on the association between shoulder subluxation and pain in patients with stroke. Method: A systematic online search was conducted of MEDLINE, EMBASE, CINAHL, AMED, Biomed Central, and the Cochrane Library. The search was supplemented by hand searching of relevant journals and citation tracking of the retrieved papers. All primary studies published in English language fulfilling the review's inclusion criteria were included. Five reviewers independently appraised the methodological quality of the selected studies. Any discrepancies were resolved following discussions. Results: Of the 148 articles that were identified by the search, 14 studies met the criteria to be included in the review. Seven studies found an association and seven studies did not find an association between subluxation and pain. The methodological quality of the studies varied considerably and studies used a wide range of outcome measures to assess both subluxation and pain. Conclusions: Irrespective of any association, both subluxation and pain can independently have an impact on functional rehabilitation. Management of these clinical outcomes is critical in clinical practice and clinicians should continue to prevent and reduce these post-stroke secondary complications to enhance upper limb function.